Pola Konsumtif Masyarakat Urban dalam Perspektif Semiotik dan Budaya - Zaman, Saefu (UI Scholars Hub, 2017)
Urban people who are migrants from rural or small town to the city have a high consumption behaviour. Consumer behaviour conducted by the urban is constituted by several reasons, such as following the metropolitan lifestyle, competing with others, improving social status, and the ease of credit card by the owners of capital. The social behaviour of people in a semiotic perspective is seen as a collection of signs. Signifier and signified is a component contained in the sign based on the views of structuralism (Saussurian). This process of understanding consumption activities does not stop at the stage of the initial or primary system. In meaning, advanced meaning or secondary system always appear. The meaning of the sign is no longer limited to the denotation meaning with a high convention but produces connotations meaning that is the result of interpretation of society. How consumption based on effort get a higher social status is a clear example of secondary meanings of consumption activities. Consumption of the particular material objects is no longer just based on the original function of the object, but rather an attempt to represent themselves to the material objects.